Job empowerment and its relationship to enhancing the organizational identity: Empirical study at Hodna Milk factory in M’sila, Algeria. - Beyragued, Abderrahmane; Helilou, Nabil (Journal of Human Sciences, 2022)
Organizational phenomena with a cultural dimension still dominate administrative theorizing because of their implications for directing and stereotyping the behavior and practices of individuals. Such as commitment and loyalty talk and organizational identity talk as an advanced level for this. The research paper is an empirical study that attempts to investigate the relationship between empowerment at work as a modern organizational phenomenon and strengthening organizational identity as a cultural dimension. She took HODNA’s Dairy as her research community, with their 169 units representing her frameworks, which were studied by the full inventory method. And because the study aims to diagnose the relationship between the variables, we adopted the descriptive and analytical method, with its only tool questionnaire form containing 38 items. And depending on the known statistical measures and methods, the statistical processing of the data obtained took place in three stages: Addressing the socio-professional characteristics, the statistical nature of the responses, then testing the relationship and discussing the hypotheses, which resulted in results and recommendations, the most important of which are; The dimensions of professional empowerment are evident / the administration strives to raise the levels of commitment and loyalty of its workers / the strengthening of the organizational identity is an ongoing process led by the dairy administration and appears in the behavior and practices of individuals.